Dietary adherence and health beliefs among Malay clients with diabetes mellitus type 2 in the diabetic centre, Hospital Universiti Sains Malaysia (HUSM) - Anshari, Rahimah Mohd (2011)
important for controlling Diabetes Mellitus Type 2. Low rate of dietary adherence had been found and health belief is considered as one of the factors that influence the performance of dietary adherence. The objective of this study was to determine the level of diabetic dietary adherence and diabetic health beliefs. A quantitative study was carried out among 136 Malay clients with OM Type 2 in Diabetic Centre, HUSM, Kelantan, Malaysia. The validated Summary Diabetes Self-Care Activities {SDSCA) scale with reliability alpha 0.68 and modified Health Belief Model Diabetes Scale with reliability alpha 0.69- 0.82 were used. Ethical clearance was obtained from Ethical and Research Committee of USM. Duration of data collection was from February to March 2009. Data were analyzed via ChiSquare and Fisher's Exact test. There were 64% respondents in this study who adhered to their diabetic dietary regimen. Majority of the respondents had high positive beliefs of diabetes on susceptibility to diabetic complication and benefit which were 90% and 95% respectively. The severity and barriers domain showed 23% of respondent had high positive belief. This study had identified that there were certain false beliefs of diabetes especially in severity and barriers domain. Perceived susceptibility, benefits, and barriers in following diabetic dietary regimens were significantly associated with diabetic dietary adherence with the p <0.0001, p = 0.009, and p = 0.028. Perceived severity showed no significant association with dietary adherence {p = 0.843). As a conclusion, the prediction of HBM is most likely true except for the perceived severity. Health care providers need to establish guideline to change false belief of diabetes and overcome the barriers among OM clients.